Preparation of Active Carbon by Additional Activation with Potassium Hydroxide and Characterization of Their Properties - Bronislaw Buczek (Advances in Materials Science and Engineering)
A commercially available activated carbon was used to prepare active carbon via reactivation with KOH at 750°C. Active carbon was obtained with 60.5% yield. The resulting active carbon showed a well-developed porous structure with specific surface area 2939 m2/g, total pore volume 1.488 cm3/g, and micropore volume 1.001 cm3/g. Process reactivation of carbon changes its particle size as well as density properties and increases by nearly twice the amounts of methane and carbon dioxide adsorbed under high pressure conditions. Such active carbon may be used to enrich methane or carbon dioxide by pressure swing adsorption technique. Other possible applications of reactivated carbon are storage of hydrogen and methane and sequestration of carbon dioxide.